Propolis bioactive compounds as potential topical agents for atopic dermatitis: an in silico pharmacokinetic screening and molecular docking study - Naura Nurnahari; Adinda Salsabila; Tantri Liris Nareswari; Inggit Ariana Herawati; Riska Arini; Melati Utami; Theresia Sarah; Yasinda Oktariza; Annisaa Siti Zulaicha (Pharmacy Department, Faculty of Health Sciences, Jenderal Soedirman University, Purwokerto, Indonesia, 2025)
Background: Atopic dermatitis (AD) is a common chronic inflammatory skin disease. Current treatments, including corticosteroids and calcineurin inhibitors, are effective but limited by long-term adverse effects. Propolis possesses antimicrobial, anti-inflammatory, antioxidant, and immunomodulatory properties. This study evaluated propolis bioactive compounds as topical therapeutic candidates for AD using molecular docking analysis. Methods: Bioactive compounds from propolis were screened for pharmacokinetic and ADMET properties relevant to topical application. Molecular docking was performed against key protein targets implicated in AD pathogenesis to evaluate binding affinities and interaction profiles versus reference ligands. Results: A total of 31 compounds fulfilled the pharmacokinetic and toxicity criteria for topical use. Tschimgin showed the strongest affinity toward secretory phospholipase A₂ (ΔG = −8.00 kcal/mol; Ki = 1.37 µM) and favorable binding to FK506-binding protein 12 (ΔG = −7.88 kcal/mol; Ki = 1.68 µM), suggesting multitarget potential. Suberosin showed the highest affinity toward PDE4 (ΔG = −6.86 kcal/mol; Ki = 9.35 µM), exceeding the reference drug roflumilast (ΔG = −6.47 kcal/mol; Ki = 18.06 µM). Conclusion: These findings suggest propolis contains bioactive compounds relevant to multiple AD-associated targets. Tschimgin and suberosin may serve as lead compounds for developing safer topical therapies, pending further in vitro and in vivo validation.